ESTABLISHMENT OF RURAL VILLAGE CENTERS AND CHANGES IN THEIR ACTIVITIES IN FERGANA REGION - Ahmedova Rashida Muqimovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the reforms carried out in the health care system in the Fergana region during the years of independence, as well as the establishment of a quality and efficient service system for the population, i.e. the establishment of rural medical centers, as well as their activities. The history of the development of rural medical centers in Fergana region and changes in the field of health care and their importance are analyzed through legal documents and periodical press materials. Also, the results of reforms created in the healthcare system in our country, existing problems are studied scientifically.